Beberapa Karakteristik Mushaf Kuno dari Situs Giri Gajah - Syaifudin Syaifuddin; Muhammad Musadad (Lajnah Pentashihan Mushaf Al-Qur'an, 2015)
Before the arrival of the printing machine in Indonesia in the early 20th, the multiplication of the Qur'an was carried out through the copying in manual process at various places. As a result of the traditional process of copying, the frequent errors occurred that cause differences between one manuscript to another. Some studies that have been done show that such differences are generally occurred in the aspects of rasm,(style of writing), punctuation, paper material, as well as the illuminations which were influenced by the culture of certain areas. This paper examines the five ancient manuscripts originating from the site of Girigajah. It is through a philological and codicological approaches that some unique and distinctive characters of the Manuscripts of Girigajah are known. The results show that the Manuscripts from the site of Girigajah which come from the 18th century to 19th AD, still use the form called 'rasm imlai', the vowel punctuation, the recitation formula (Tajwid) and the waqaf (the sign to stop) which is fairly complete, as well as beautiful illumination, a combination of local style and the influence of Middle Eastern style.